Meningkatkan Aktivitas dan Prestasi Belajar Pendidikan Agama Hindu dan Budi Pekerti Melalui Penerapan Metode Diskusi Dikombinasikan Dengan Metode Project Based Learning - Padmawati, Ketut Ayu; Subrata, I Gede Harja; Suastini, Ni Nyoman (STKIP AGAMA HINDU SINGARAJA, 2023)
Based on observations, activities and learning achievement of class X RPL SMK TI Bali Global Singaraja, it can be categorized as very low. Judging from the above phenomena, this study aims to increase the activity and learning achievement of class X RPL students at SMK TI Bali Global Singaraja by trying to apply the discussion method combined with the project based learning method. The research subjects were class X RPL SMK TI Bali Global Singaraja Academic Year 2022/2023. In this study, the Discussion method was used combined with the Project Based Learning Method in the subjects of Hinduism and Morals. In this study the researchers set targets in the class average (M) 80, Absorption Power (DS) 80%, Mastery Learning Classical 80% and activity 80%. Judging from the results of this study, that the application of the Discussion method combined with the Project based learning method can increase learning activity and achievement in the subjects of Hinduism and morals. These results are indicated by an increase in the results of learning activities in the first cycle of 31% and the second cycle to 85%. Student achievement also increased, namely in the first cycle the class average (M) was 70, the absorption power (DS) was 70%, the learning mastery was 22% and the second cycle became the class average (M) 89, the absorption power (DS) was 89% , as well as 100% classical learning completeness from KKM 75. From the research results that have been achieved this can be implemented by recommending all Hindu Religion Teachers, especially Hindu Religion teachers to apply the Discussion method combined with the project based learning method as an effort to improve the quality and quality of student education in the field of Hindu religious and moral education, in the form of evidence of students' learning activities and achievements that are getting better.